Bernabé, Alberto; García Gual, Carlos; Lemosín, Rogelio; Pirart, Eric. Mitología y Religión del Oriente Próximo Antiguo, III. Indoeuropeos. - Álvarez Pedrosa Núñez, Juan Antonio ('Ilu. Revista de Ciencias de las Religiones, 2000)
Sin resumen